2016
DOI: 10.1007/s11192-016-2059-2
|View full text |Cite
|
Sign up to set email alerts
|

At what institutions did Nobel laureates do their prize-winning work? An analysis of biographical information on Nobel laureates from 1994 to 2014

Abstract: In this study we examined the institutions (and countries) the Nobel laureates of the three disciplines chemistry, physics and physiology/medicine were affiliated with (from 1994 to 2014) when they did the decisive research work. To be able to frame the results at that time point, we also looked at when the Nobel laureates obtained their Ph.D./M.D. and when they were awarded the Nobel Prize. We examined all 155 Nobel laureates of the last 21 years in physics, chemistry, and physiology/medicine. Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 51 publications
0
45
0
1
Order By: Relevance
“…In a further study Chan et al [7] also found that publications of Nobel Laureates with collaborators tended to be cited more if they were work done early in the time span of the collaboration. In another study Schlagberger et al [8] looked at the affiliated institutions of Nobel Laureates from physics, chemistry and medicine/physiology. The finding was that as a country USA dominated in the number of affiliated Laureates, and the three institutions that was found to contain a larger number of Laureates at all time, UC Berkeley, Columbia University and the Massachusetts Institute of Technology (MIT), are also located there.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a further study Chan et al [7] also found that publications of Nobel Laureates with collaborators tended to be cited more if they were work done early in the time span of the collaboration. In another study Schlagberger et al [8] looked at the affiliated institutions of Nobel Laureates from physics, chemistry and medicine/physiology. The finding was that as a country USA dominated in the number of affiliated Laureates, and the three institutions that was found to contain a larger number of Laureates at all time, UC Berkeley, Columbia University and the Massachusetts Institute of Technology (MIT), are also located there.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Nobel prize is undoubtedly the most visible, influential, and coveted award across science. Nobel laureates represent a readily demarcated and most illustrious cohort of exceptional scientists, and data on their work have been repeatedly used [1][2][3][4][5][6][7][8][9][10][11][12][13][14] to assess aspects of citation impact, perception of rewards, credit allocation, paradigm shifts, and networking in science. Much can be learned by studying this influential cohort.…”
Section: Introductionmentioning
confidence: 99%
“…to the Nobel Prize, the research of the Turing Award is relatively incomprehensive. There exist several works devoted to studying relevant attributes of the Nobel Prize [2] and the Nobel Prize laureates [3] while the research of the Turing Award is particularly rare. As the highest prize in the field of computer science, we believe that the analysis of the Turing Award can highlight the important contributions of the Turing Award laureates.…”
Section: Introductionmentioning
confidence: 99%